A Research Study on the Contemporary Relevance and Application of Quranic Dialogues - Ummi Tehmiya; Dr. Sadiq Ali* (Journal of Religion and Society, 2025)
The Qur’an presents dialogues between God and humankind, between prophets and their communities, and between the representatives of truth and falsehood in a highly profound and purposeful style. These dialogues are not merely historical accounts but carry eternal messages that continue to provide guidance in every era. The aim of this research is to examine how the Qur’anic dialogues hold significance in the contemporary world and how they can be applied to present-day intellectual, social, and moral challenges. This study particularly explores their relevance to modern existential questions, interfaith and intercultural dialogues, and the growing need for social harmony. The findings suggest that Qur’anic dialogues not only provide theological and ethical insights but also serve as foundational frameworks for conflict resolution, education, moral training, and the development of both individual and collective character. Thus, their contemporary relevance lies in awakening human consciousness, transforming conflict into dialogue, and guiding humanity towards purpose, wisdom, and intellectual growth.